MENINGKATAN KEMAMPUAN MENYIMAK MELALUI BERCERITA BERBASIS CERITA RAKYAT PADA ANAK - PURIDAWATY, BRIGITA (PPs UNJ, 2011)
The objective of this research is to know: the learning process to increase the listening ability kindergarten student through storytelling based on folktales and change of listening ability after the implementation. 12 students of Nita kindergarten Maumere are the research subject. This research uses action research method according to Kemmis and Mc Taggart that consist of four steps: plan, action, observation, and reflection. Data collecting techniques uses field notes, interview, documentation, and observation. This research uses descriptive analysis. The result of the research describe that storytelling based on folktales gives impact for increasing listening ability of 4-5 years old. The result shows increase of 65,3% and the observation shows more than 75% students get good mark.Keywords: listening, storytelling